The effect of D,L-β-aminobutyric acid on the growth and development of Fusarium oxysporum f. sp. tulipae (Apt.) - Anna Jarecka (Acta Agrobotanica, 2012)
The effect of D,L-β-aminobutyric acid (BABA) on the growth and development of the root system and the development of fusariosis on tulip bulbs cv. Apeldoorn infected by Fusarium oxysporum f. sp. tulipae (F.ox.t. 218) was studied. The length and fresh weight of roots, the development of fusariosis on bulbs and the linear growth of mycelium of F.ox.t. 218 on PDA medium were measured. Preventively used BABA at a concentration of 100, 250 and 300 µg·cm-3 for soaking uncooled and cooled tulip bulbs greatly inhibited the development of fusariosis on the root system; the length and fresh weight of roots were similar to those of the bulbs not inoculated with F.ox.t. 218. At a concentration of 100 µg·cm-3;, BABA used for soaking bulbs limited the development of fusariosis on scales in about 50% and the concentration of 200 µg·cm-3 totally inhibited the disease symptoms induced by F.ox.t. 218. At a concentration of 100 - 1000 µg·cm-3, BABA did not inhibit the mycelium growth of F.ox.t. 17 and F.xo.t. 218 on PDA medium. This study suggests that BABA protects tulip roots and bulb scales against F. oxysporum f. sp. tulipae by inducing resistance in these organs and has no direct influence on the pathogen.